Rate of endomycorrhizal colonization in Pistacia vera L. - Bouabdelli Z.; Belhadj S.; Sadoun Smail N. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In arid areas, plants develop several strategies to adapt to bad conditions of survival especially drought. To resist, they develop associations with symbiotic fungi: mycorrhizae. The object of our study is to know the influence of seasonal variation (spring and winter) on root colonization rates by these fungi. For this purpose we chose Pistacia vera L., a fruit species cultivated in the orchard of Ross-Loayone located in the province of Djelfa in Algeria. The soil analysis have revealed that the soil is not salty, has high total calcium and is rich in organic matter. Microscopic observations showed the presence of endomycorrhizae-type fungal structures belonging to the class of Glomyromycètes. These fungal structures are vesicles, arbuscules and siphoned hyphae. T-test shows that there is a highly significant difference at p <0.001 between two seasons for the number of vesicles and arbuscules per fragment, that they are higher in the spring and that there is a good positive correlation between them. The hyphae are siphoned intra and extra –roots, and they are present at high rate in the winter.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)